240-GHz Four-Channel Power-Tuning Heterodyne Sensing Readout System With Reflection and Transmission Measurements in a 130-nm SiGe BiCMOS Technology - Defu Wang, Mohamed Hussein Eissa, Klaus Schmalz, Jongwon Yun, Andrea Malignaggi, Johannes Borngräber, Maciej Kucharski, Thomas K (IEEE Transactions on Microwave Theory and Techniques, 2019)
This article presents a fully differential power-tuning heterodyne on-chip sensing readout system at 240 GHz. The chip enables the measurement of not only the transmission parameter but also the reflection parameter to sense the permittivity of different materials by using four heterodyne mixer-based receiving channels connected to a dielectric sensing element. To facilitate the operation and characterization, three frequency multiplier chains are included to generate the required two identical radio frequency (RF) and one local oscillator (LO) subterahertz signals. RF frequency multiplier chain is configured to enable a tunable power level of the RF signal by using a variable attenuator. A chip prototype using 130-nm silicon–germanium (SiGe) BiCMOS is implemented with a size of 11 mm 2 and dc power consumption of 2.7 W. The measured 10-dB bandwidth of 20.8% is achieved in a frequency range from 207 to 257 GHz with 14-dB measured power-tuning range. The transmission and reflection parameters’ measurements for copper and gummi show a differentiated value in terms of magnitude and phase, which demonstrates the sensing function of the proposed readout system.